Acciones antropogénicas en el área de influencia norte de la Represa BABA y su impacto en la calidad del agua. Año 2012. Plan de acción ambiental. - Prieto Benavides, Oscar Oswaldo (2013)
In this study was evaluated the anthropogenic activities developed in the northern hinterland Baba Dam affect water quality, for the evaluation of water quality indices were used BMWP-CO and ETP, that were employed on the basis of identifying aquatic macroinvertebrates present in the study area and also physical-chemical analyzes of water and applied surveys for the assessment of the residents of the sector. The result of the application of water quality indices and ETP BMWP-CO show that the water in the northern hinterland Baba Dam is fair to poor, that is contaminated, home to as many specimens that accept contaminants. It was found a total of 3190 specimens belonging to 6 orders and 9 families in the 6 sampling stations were previously identified in the sector. The 24 surveys that were applied to the residents of the sector showed that there is evidence of contamination, a large percentage usually observed that develop harmful activities such as air and ground fumigation, spray wash pumps and pesticides, etc.. With respect to physical and chemical analysis conducted in the study area Dissolved Oxygen, Biological Oxygen Demand (BOD) Chemical Oxygen Demand (COD) and Total Suspended Solids (TSS), all they are outside the maximum permissible for good water quality except SST.